Gender and Reprimands in an Academic Circle: Evidence from an Iraqi EFL Context. - عباس غبن الزبيدي, نصير (Al-Adab Journal, 2018)
The study examines the pragmatic strategies of reprimanding behavior by Iraqi EFL male and female university learners and identifies the politeness strategies preferred by each gender. A discourse-completion task is utilized to elicit written responses from 40 Iraqi EFL participants divided equally into 20 males and 20 females. Results reveal that both Iraqi EFL male and female participants opt for solidarity politeness over deferential politeness thereby reflecting their preference for being authoritative while maintaining friendliness. As for supportive moves, they use mitigators and aggravators to ameliorate and intensify respectively the head acts of reprimands. They prefer aggravators over mitigators in their reprimands. Though the two gender groups of Iraqi EFL participants use the same strategy types of head acts and supportive moves in their reprimands, they differ in the frequency of occurrence of particular strategy types. Finally, a number of conclusions and pedagogical implications are presented.